San Francisco Opera Company... October 23 through November 4, 1954 - San Francisco Opera::::::::::::::: (Los Angeles, CA; United States; John F. Huber, 2022)
Program booklet for the San Francisco Opera performances from October 23-November 4, 1954, including a performance of Fidelio on October 25, 1954, at the Shrine Auditorium, Los Angeles.